A Comparative Study Using WHO and Binary Oral Epithelial Dysplasia Grading Systems in Leukoplakic Lesions: Epithelial dysplasia grading in leukoplakic lesions - Atarbashi-Moghadam, Saede; Sandoghdaran , Sara; Rakhshan, Azadeh; Mirebeigi Jamasbi, Seyed Sepehr (Journal of Dental School, 2024)
Objectives This study aimed to compare the reproducibility and consistency of the World Health Organization (WHO) and Binary oral epithelial dysplasia grading systems when applied to leukoplakic lesions, the most common oral potentially malignant disorders (OPMDs). Methods In this retrospective, cross-sectional study, clinical data and microscopic slides of 89 leukoplakia cases were reviewed. Two pathologists independently graded each sample using both WHO and Binary systems. Inter-observer agreement was evaluated using kappa statistics. The relationship between variables and the grade of dysplasia was analyzed using T-test and Chi-square test at p<0.05. Results The mean age of cases was 53.93 ± 13.84 years, with a slight female predominance. The lesions were most commonly located on the tongue (38.2%) and buccal mucosa (37.08%). The inter-observer agreement was higher for the Binary system (kappa index= 0.62) compared to the WHO system (kappa index= 0.46). The highest agreement was observed for cellular features such as the increased number of cell nucleoli (0.74) and cell pleomorphism (0.73), while keratin pearls showed the lowest agreement (0.21). Conclusion The Binary classification system demonstrated superior consistency and reproducibility compared to the WHO system due to fewer grading categories. However, its detailed numerical requirements and time-consuming nature may limit its widespread adoption, which is why the WHO system is more commonly used.